Toward an environmental strategy for Asia a summary of a World Bank discussion paper - Brandon, Carter 1954-; Ramankutty, Ramesh 1960- (World Bank, 1993)
A summary of a longer paper by the two authors published as no. 224 of the World Bank discussion papers.